2018
DOI: 10.1016/j.paid.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The relations between processing style, autistic-like traits, and emotion recognition in individuals with and without Autism Spectrum Disorder

Abstract: Kris (2018) The relations between processing style, autistic-like traits, and emotion recognition in individuals with and without Autism Spectrum Disorder. Personality and Individual Differences, 120. pp. 1-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
(42 reference statements)
4
20
0
Order By: Relevance
“…The ER measure was piloted with two groups: adults (N = 22, male = 10, M age = 32.41, SD = 12.05) and children (N = 27, male = 26, M age = 10.96, SD=3.01). This pilot found the pattern of identification of emotions was broadly similar to that found in other studies using static emotion stimuli with context (McKenzie et al, 2018), with the exception of disgust and boredom. The latter emotions had considerably lower accuracy levels, perhaps reflecting the increased challenge of processing more complex emotions when they are presented dynamically Each emotion was displayed with and without situational cues.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The ER measure was piloted with two groups: adults (N = 22, male = 10, M age = 32.41, SD = 12.05) and children (N = 27, male = 26, M age = 10.96, SD=3.01). This pilot found the pattern of identification of emotions was broadly similar to that found in other studies using static emotion stimuli with context (McKenzie et al, 2018), with the exception of disgust and boredom. The latter emotions had considerably lower accuracy levels, perhaps reflecting the increased challenge of processing more complex emotions when they are presented dynamically Each emotion was displayed with and without situational cues.…”
Section: Methodssupporting
confidence: 87%
“…The continuum theory of ASD proposes that individuals in the general population vary in the extent to which they have autistic like traits (ALT) and that those with a diagnosis of ASD have higher/more extreme levels of the relevant traits (see Murray et al, 2014). Recent research has found that individuals with higher levels of autistic like traits (ALT) showed significantly poorer ER (e.g., McKenzie et al, 2018). It is, therefore, possible to extrapolate findings from a sub-clinical sample to those with a formal diagnosis of ASD, whilst avoiding some of the methodological constraints associated with using a clinical sample (Lord et al, 2005;Murray et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 59 of this subsample reported their occupational status as employed, 14 as unemployed, 84 as student, and 4 as school pupil. The third nonclinical subsample ( n = 238, 28% male) was recruited for a study on emotion recognition (McKenzie et al, 2018). This subsample has a mean age of 29.8 ( SD = 13.17).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to contracts, the economic linkages between companies and those in the poultry farming industry have also increased exceptionally in the last twenty years. Research studies on poultry farming in Asia and Africa (Williams et al, 2017) illustrate the growth of poultry in the last two decades, McKenzie et al (2018) examine the contract relationships between the poultry growers and suppliers which has resulted in an incredible growth of poultry production and increase in the performance of poultry business. With the growth in livestock, a need is also felt to create effective product supply chains in order to sustain, modulate and promote livestock in particular and agriculture and globalization also in general.…”
Section: Introductionmentioning
confidence: 99%